2022
DOI: 10.1186/s12879-022-07517-w
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and quality-of-life in the year following SARS-Cov2 infection

Abstract: Background The SARS-COV2 pandemic has been ongoing worldwide since at least 2 years. In severe cases, this infection triggers acute respiratory distress syndrome and quasi-systemic damage with a wide range of symptoms. Long-term physical and psychological consequences of this infection are therefore naturally present among these patients. The aim of this study was to describe the state of health of these patients at 6 (M6) and 12 months (M12) after infection onset, and compare quality-of-life (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…The relatively high regression coefficient for the fatigue severity suggests that this may have a greater impact on overall HRQoL than other symptoms. A significant impact of fatigue on the HRQoL has been reported in previous studies in younger populations [ 41 , 42 ] as well and suggested early monitoring of fatigue and its associated symptoms in post-COVID-19 survivors [ 42 ]. Fatigue has been recognized as one of the most disabling complaints in individuals recovered from coronavirus infection [ 43 ].…”
Section: Discussionmentioning
confidence: 86%
“…The relatively high regression coefficient for the fatigue severity suggests that this may have a greater impact on overall HRQoL than other symptoms. A significant impact of fatigue on the HRQoL has been reported in previous studies in younger populations [ 41 , 42 ] as well and suggested early monitoring of fatigue and its associated symptoms in post-COVID-19 survivors [ 42 ]. Fatigue has been recognized as one of the most disabling complaints in individuals recovered from coronavirus infection [ 43 ].…”
Section: Discussionmentioning
confidence: 86%
“…This data extend to 18 months previously reported PASC symptoms and associations with QoL measures at earlier time points. [7][8][9][10][11] Fatigue, brain fog, nasal congestion and discharge, headache, sleep disturbances, and body aches were the most common symptoms. Neurological, mood, and systemic symptoms persisted in over half of participants surveyed at 18 months post-COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Aproximadamente 20% das pessoas infectadas apresentam quadros graves da doença e necessitam de hospitalização, geralmente com quadros de pneumonia, evoluindo, entre outros casos, à síndrome respiratória aguda grave (Chen et al, 2020;WHO, 2022b;Zeiser et al, 2022;Zhu et al, 2020). Além disso, alguns sinais e sintomas, como confusão mental, anosmia e disgeusia podem ser persistentes em algumas pessoas que tiveram COVID-19, porém o porquê de isso acontecer ainda é incerto e debatido na literatura (Noujaim et al, 2022).…”
Section: Aspectos Epidemiológicos E Clínicos Das Infecções Por Sars-c...unclassified